Altered levels of blood proteins in Alzheimer's disease longitudinal study: Results from Australian Imaging Biomarkers Lifestyle Study of Ageing cohort. Issue 1 (22nd April 2017) - Gupta, Veer Bala; Hone, Eugene; Pedrini, Steve; Doecke, James; O'Bryant, Sid; James, Ian; Bush, Ashley I.; Rowe, Christopher C.; Villemagne, Victor L.; Ames, David; Masters, Colin L.; Martins, Ralph N.; et al.
Abstract: Introduction: A blood‐based biomarker panel to identify individuals with preclinical Alzheimer's disease (AD) would be an inexpensive and accessible first step for routine testing. Methods: We analyzed 14 biomarkers that have previously been linked to AD in the Australian Imaging Biomarkers lifestyle longitudinal study of aging cohort. Results: Levels of apolipoprotein J (apoJ) were higher in AD individuals compared with healthy controls at baseline and 18 months ( P = .0003) and chemokine‐309 (I‐309) were increased in AD patients compared to mild cognitive impaired individuals over 36 months ( P = .0008). Discussion: These data suggest that apoJ may have potential in the context of use (COU) of AD diagnostics, I‐309 may be specifically useful in the COU of identifying individuals at greatest risk for progressing toward AD. This work takes an initial step toward identifying blood biomarkers with potential use in the diagnosis and prognosis of AD and should be validated across other prospective cohorts.